Screening for iron deficiency and iron deficiency anaemia in pregnancy: a structured review and gap analysis against UK national screening criteria. - Rukuni, R; Knight, M; Murphy, M; Roberts, D; Stanworth, S (BioMed Central, 2015)
Background Iron deficiency anaemia is a common problem in pregnancy despite national recommendations and guidelines for treatment. The aim of this study was to appraise the evidence against the UK National Screening Committee (UKNSC) criteria as to whether a national screening programme could reduce the prevalence of iron deficiency anaemia and/or iron deficiency in pregnancy and improve maternal and fetal outcomes. Methods Search strategies were developed for the Cochrane library, Medline and Embase to identify evidence relevant to UK National Screening Committee (UKNSC) appraisal criteria which cover the natural history of iron deficiency and iron deficiency anaemia, the tests for screening, clinical management and evidence of cost effectiveness. Results Many studies evaluated haematological outcomes of anaemia, but few analysed clinical consequences. Haemoglobin and ferritin appeared the most suitable screening tests, although future options may follow recent advances in understanding iron homeostasis. The clinical consequences of iron deficiency without anaemia are unknown. Oral and intravenous iron are effective in improving haemoglobin and iron parameters. There have been no trials or economic evaluations of a national screening programme for iron deficiency anaemia in pregnancy Conclusion Iron deficiency in pregnancy remains an important problem although effective tests and treatment exist. A national screening programme could be of value for early detection and intervention. However, high quality studies are required to confirm whether this would reduce maternal and infant morbidity and be cost effective